Family Caregiving and the Intergenerational Transmission of Poverty. Issue 3 (September 2018) - Kaplan, Richard L.
The United States relies on uncompensated family caregivers to provide most of the long-term care required by older adults as they age. But such care comes at a significant financial cost to these caregivers in the form of lower lifetime earnings and diminished (or even no) Social Security retirement benefits, ineligibility for Medicare coverage of their healthcare costs, and minimal retirement savings. To reduce the impact of uncompensated caregiving on the intergenerational transmission of poverty, this paper discusses three possible mechanisms of compensating family caregivers: public payments, deemed wage credits under Social Security, and income tax incentives.